Предмет: Математика,
автор: Ivan1234567890010
{15+2(Х+3у )=3(4Х+у)
{2(5х-у)-3у=2+3(2х-у)
Ответы
Автор ответа:
0
{15+2х+6у=12х+3у
{10х-2у-3у=2+6х-3у
↓
{15 = 10х-3у
{4х -2у=2
↓
{15=10х-3у
{2 (2х-у)=2
↓
{15=10х - 3у (1)
{2х - у=1 (2) => 2х-1=у
подставляем в (1), получаем
15=10х - 3 (2х-1)
15=10х - 6х +3
12= 4х
х = 12/4=3
(2) у = 2*3-1= 5
отв: 3; 5
{10х-2у-3у=2+6х-3у
↓
{15 = 10х-3у
{4х -2у=2
↓
{15=10х-3у
{2 (2х-у)=2
↓
{15=10х - 3у (1)
{2х - у=1 (2) => 2х-1=у
подставляем в (1), получаем
15=10х - 3 (2х-1)
15=10х - 6х +3
12= 4х
х = 12/4=3
(2) у = 2*3-1= 5
отв: 3; 5
Похожие вопросы
Предмет: Українська мова,
автор: vikabutlerska
Предмет: История,
автор: veronikadovgajlo7
Предмет: История,
автор: irinapshenixnix
Предмет: Алгебра,
автор: Аноним
Предмет: История,
автор: 55yano4ka55